(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2022)
Forty samples of Gibin al Arab cheese were collected from local market at Babylon province for studying the microbial contamination ( bacterial and fungal growth ). first the study revealed that there was negative samples for each culture media used for bacterial detection, in MSA there was 27+ve samples and 13-ve samples, EMB with 24+ve samples and 16-ve samples, MRS with 32+ve samples and 8-ve samples finally S-S agar with 31+ve samples and 9 –ve samples. MSA record 17 strain of Staphylococcus aureus, 10 strain of Staphylococcus epidermidis, EMB record 12 strain of Escherichia coli, 18 strain of Klebsiella, MRS record 32 strain of Lactobacillus, S-S agar record 10 strain of Salmonella, 29 strain of Shigella. while fungi isolated on PDA was : Penicillium digitatum (74.7%), Penicillium italicum (13.2%), Penicillium citrinum (6.02 %), Penisillium chrysogenum (2.40%), Aspergellus nedulans (3.7 %), Alternaria (0%), Candida spp. with more isolates, also Rhodotorella more. MEA media used for fungi isolation record : Penicillium digitatum(80%), Penicillium italecum (3.1%), Penicillium citrinm (0%), Penicillium chrysogenum (6.2%), Aspergillus nidulans (7.69%), Alternaria ( 3.1% ), Candida spp. with more isolates, Rhodotorella more like on PDA.